Epigenetic regulation of CD133 and tumorigenicity of CD133 positive and negative endometrial cancer cells - Borger Darrell R; Belden Sarah E; Sergent Petra A; Therrien Vanessa A; Curley Michael D; Zhang Ling; Friel Anne M; Mohapatra Gayatry; Zukerberg Lawrence R; Foster Rosemary; Rueda Bo R (BMC, 2010)
Abstract Background Recent data provide significant evidence to support the hypothesis that there are sub-populations of cells within solid tumors that have an increased tumor initiating potential relative to the total tumor population. CD133, a cell surface marker expressed on primitive cells of neural, hematopoietic, endothelial and epithelial lineages has been identified as a marker for tumor initiating cells in solid tumors of the brain, colon, pancreas, ovary and endometrium. Our objectives were to assess the relative level of CD133 expressing cells in primary human endometrial tumors, confirm their tumorigenic potential, and determine whether CD133 expression was epigenetically modified. Methods We assessed CD133 expression in primary human endometrial tumors by flow cytometry and analyzed the relative tumorigenicity of CD133+ and CD133- cells in an in vivo NOD/SCID mouse model. We assessed potential changes in CD133 expression over the course of serial transplantation by immunofluorescence and flow cytometry. We further examined CD133 promoter methylation and expression in normal endometrium and malignant tumors. Results As determined by flow cytometric analysis, the percentage of CD133+ cells in primary human endometrial cancer samples ranged from 5.7% to 27.4%. In addition, we confirmed the tumor initiating potential of CD133+ and CD133- cell fractions in NOD/SCID mice. Interestingly, the percentage of CD133+ cells in human endometrial tumor xenografts, as evidenced by immunofluorescence, increased with serial transplantation although this trend was not consistently detected by flow cytometry. We also determined that the relative levels of CD133 increased in endometrial cancer cell lines following treatment with 5-aza-2'-deoxycytidine suggesting a role for methylation in the regulation of CD133. To support this finding, we demonstrated that regions of the CD133 promoter were hypomethylated in malignant endometrial tissue relative to benign control endometrial tissue. Lastly, we determined that methylation of the CD133 promoter decreases over serial transplantation of an endometrial tumor xenograft. Conclusions These findings support the hypotheses that CD133 expression in endometrial cancer may be epigenetically regulated and that cell fractions enriched for CD133+ cells may well contribute to endometrial cancer tumorigenicity, pathology and recurrence.